2023
DOI: 10.46627/silet.v3i3.116
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Hybrid Learning and Its Impacts at A Public Junior School in Indonesia

Abstract: The pandemic of COVID-19 has made several change to the learning process in Indonesia. Because of the less effective online learning, the Indonesian Ministry of Education and Culture creates new policies by allowing offline learning, but with a limited system or hybrid learning. The purpose of this study was to find out how the implementation of hybrid learning in schools, where placed at a Public Junior School in Indonesia. The type of this research is a qualitative research using interview and observation te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…This kind of learning approach has further increased access to learning materials and allowed students to study according to their pace and time, hence, with due consideration of the differing needs and schedules. However, among them, some of the previous comparative studies found the hybrid model assures the greatest learning effectiveness and an improved inclusive learning environment than those assured by learning only solely online or traditional mode (Riski Dwi et al, 2023). Comparative studies highlight the hybrid model's ability to foster a more inclusive learning environment compared to fully online or traditional methods, echoing findings from international contexts that emphasize its flexibility and adaptability (Tarigan et al, 2022).…”
Section: Results and Discussion A Blended Learning Models In Indonesi...mentioning
confidence: 99%
“…This kind of learning approach has further increased access to learning materials and allowed students to study according to their pace and time, hence, with due consideration of the differing needs and schedules. However, among them, some of the previous comparative studies found the hybrid model assures the greatest learning effectiveness and an improved inclusive learning environment than those assured by learning only solely online or traditional mode (Riski Dwi et al, 2023). Comparative studies highlight the hybrid model's ability to foster a more inclusive learning environment compared to fully online or traditional methods, echoing findings from international contexts that emphasize its flexibility and adaptability (Tarigan et al, 2022).…”
Section: Results and Discussion A Blended Learning Models In Indonesi...mentioning
confidence: 99%